Bridging Research Competencies and Outcomes: Technological Skills Lead-ing The 21st-Century Research Era - Potot, Kenneth June S.; Dacanay, Lorlaine R.; Moneva, Jerald C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
With the researcher’s assumption that a specific research skill may positively contribute to the learners’ research output, a 240-item standardized test question was conducted among the 231 grade 12 students. The questionnaires are fitted according to the DepEd self-learning modules from the senior high school curriculum. This study developed a model to examine the relationship between the grade 12 students' research skills and their research output. Statistical analysis revealed that learners scored low in Data Analysis, Critical Thinking, and Interpreting Result, with mean scores of 47.4, 44.9, and 43.6, re-spectively. Ran through Jamovi version 2.3.28 software, the correla-tion matrix revealed that six of the eight identified research skills sta-tistically significant to the research output were used for confirmato-ry factor analysis. Two research skills used for the mediation model stood out from the rest. The Information & Literacy skills were better suited to mediate Technological skills and research output compared to Technological skills alone. The model demonstrated a strong rela-tionship between the independent variable-Technological skills, and the dependent variable- their ability to conduct effective research.